Answer Identification from Product Reviews for User Questions by Multi-Task Attentive Networks - Chen, Long; Guan, Ziyu; Zhao, Wei; Zhao, Wanqing; Wang, Xiaopeng; Zhao, Zhou; Sun, Huan (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Online Shopping has become a part of our daily routine, but it still cannot offer intuitive experience as store shopping. Nowadays, most e-commerce Websites offer a Question Answering (QA) system that allows users to consult other users who have purchased the product. However, users still need to wait patiently for others’ replies. In this paper, we investigate how to provide a quick response to the asker by plausible answer identification from product reviews. By analyzing the similarity and discrepancy between explicit answers and reviews that can be answers, a novel multi-task deep learning method with carefully designed attention mechanisms is developed. The method can well exploit large amounts of user generated QA data and a few manually labeled review data to address the problem. Experiments on data collected from Amazon demonstrate its effectiveness and superiority over competitive baselines.